2023
DOI: 10.1002/batt.202200565
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Electrochemical and Interfacial Behavior of Sulfolane based Electrolyte in LiNi0.5Mn1.5O4‐Graphite Full‐Cells

Abstract: An ethylene carbonate‐free electrolyte composed of 1 M lithium bis(fluorosulfonyl) imide (LiFSI) in sulfolane (SL) is studied here for LiNi0.5Mn1.5O4‐graphite full‐cells. An important focus on the evaluation of the anodic stability of the SL electrolyte and the passivation layers formed on LiNi0.5Mn1.5O4 (LNMO) and graphite is being analysed along with intermittent current interruption (ICI) technique to observe the resistance while cycling. The results show that the sulfolane electrolyte shows more degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…An increase of about 12 mbar is observed during the first charge, indicating a similar initial formation of CEI and SEI, as observed in an earlier work by our group. 40 However, in the subsequent cycles, the pressure evolution seems to stabilize for PAA, whereas it continues to increase for the CMC binder. From the capacity curves, in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…An increase of about 12 mbar is observed during the first charge, indicating a similar initial formation of CEI and SEI, as observed in an earlier work by our group. 40 However, in the subsequent cycles, the pressure evolution seems to stabilize for PAA, whereas it continues to increase for the CMC binder. From the capacity curves, in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The oxidative reaction of GaSn started at ≈3 V on the higher voltage side, and the reductive reaction was observed at ≈1 V on the lower voltage side. Because the highly concentrated electrolytes ([Li(G4)][TFSI] and [Li(SL) 3 ][FSI]) used in this experiment have wide electrochemical potential windows in the range of 0-4 V versus Li/Li þ , [27,28] the oxidative and reductive currents at ≈3 and 1 V, respectively, can be attributed to the electrochemical reaction of GaSn. It has been reported that the potential window of EGaIn, a Ga-based liquid metal, is 2 V in ionic liquid electrolytes in which an oxidative current was observed at ≈À0.2 V versus Ag/AgCl (corresponding to ≈3 V vs Li/Li þ ).…”
Section: Evaluation Of Conductive Substrates As Coin Cellsmentioning
confidence: 99%